Cardiac Murmurs in Children - O.P. Volosovets; S.P. Kryvopustov; O.L. Kovalchuk; T.I. Shevtsova; A.V. Kupkina (Zaslavsky O.Yu., 2015)
The lecture deals with the questions of evaluating auscultation pattern of the cardiac murmurs in children. The classification of cardiac murmurs in children, mechanisms of the onset of organic and functional murmurs were analyzed. In particular, their differentiation was described by such indicators as the phase of occurrence, the epicenter of murmur, intensity, tone, irradiation, dependence on the respiratory phase, on the position of a child, on physical exertion and others. The attention is focused on the physician's approach in detecting various cardiac murmurs in children.